Design, Synthesis and Anti-Lung Cancer Evaluation of 1, 2, 3-Triazole Tethered Dihydroartemisinin-Isatin Hybrids - Hou, Haodong; Qu, Bin; Su, Chen; Hou, Guihua; Gao, Feng (Frontiers in Pharmacology, 2021)
A series of 1,2,3-triazole tethered dihydroartemisinin-isatin hybrids 8a-c and 9a-k were designed and synthesized. Their antiproliferative activity against A549, doxorubicin-resistant A549 (A549/DOX) as well as cisplatin-resistant A549 (A549/DDP) lung cancer cell lines was also investigated in this study. All hybrids (half maximal inhibitory concentration/IC50: 7.54-73.8 μM) were more potent than the parent drug dihydroartemisinin (IC50: 69.4-88.0 μM) and also non-cytotoxic towards mouse embryonic fibroblast cells NIH/3T3 (IC50: >100 μM). The structure-activity relationships illustrated that the substituents on C-3 and C-5 position of isatin moiety influenced the activity significantly. Imine at C-3 position decreased the activity, whereas fluoro at C-5 position enhanced the activity. In particular, hybrids 8a,c (IC50: 7.54-12.1 μM) and 9i (IC50: 9.10-15.9 μM) were comparable to cisplatin (IC50: 7.54-15.9 μM vs 9.38-19.7 μM) against A549 and A549/DOX, but 4.6-7.6 folds more potent than that of cisplatin (IC50: 8.77-14.3 μM vs 66.9 μM) against A549/DDP cells. Moreover, hybrids 8a,c exhibited excellent stability (liver microsomes: 68%-83%) in mouse/human microsomes and good pharmacokinetic properties, demonstrating their potential as a novel anti-lung cancer chemotherapeutic candidates.